Homelessness Prevention and Intervention in Social Work Policies, Programs, and Practices - Larkin, Heather; Aykanian, Amanda; Streeter, Calvin L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This important text provides a comprehensive survey of homelessness in America: its scope and causes, its diverse populations, and the array of responses at the individual, community, and systems levels. Expert contributors explore the links between trauma and homelessness, the cycle of homelessness and health/mental health problems, and barriers preventing people from accessing services. Case studies of effective programs and practices focus on science-based interventions, broad understanding of client needs, and close coordination between systems and agencies. Finally, specialized chapters discuss issues and experiences common to homeless youth and young adults, including housing instability on college campuses and empowerment-based strategies for engaging youth voice in programming . Included in the coverage: Homelessness and health disparities: a health equity lens Affordable housing and housing policy responses to homelessness Street talk: homeless discourses and the politics of service provision Multisectoral collaborations to address homelessness Trauma-informed care in homelessness service settings: challenges and opportunities Incorporating youth voice into services for young people experiencing homelessness Homelessness Prevention and Intervention in Social Work fills a critical gap in the social work curriculum as a main or a supplementary text. It also makes an accessible resource for clinicians and community practitioners seeking current knowledge on the topic, practical approaches to working with clients experiencing homelessness, and useful information for effective program and policy design.
Part I: Characteristics and Service Needs of People Experiencing Homelessness -- Homelessness in America: An Overview -- Trauma and Adversity in the Lives of People Experiencing Homelessness -- Homelessness and Health Disparities: A Health Equity Lens -- Meeting the Diverse Service Needs of People Experiencing Homelessness -- Part II: Individual, Community, and System Responses to Homelessness -- Affordable Housing and Housing Policy Responses to Homelessness -- Street Talk: Homeless Discourses and the Politics of Service Provision -- Community-Based Strategies to Address Homelessness -- Homelessness in Los Angeles and New York City: A Tale of Two Cities -- The Criminalization of Homelessness -- Pay-for-Success Financing: Innovation in Funding Supportive Housing Initiatives -- Part III: Homelessness Services Delivery -- Critical Time Intervention -- Multisectoral Collaborations to Address Homelessness -- Trauma-Informed Care in Homelessness Service Settings: Challenges and Opportunities -- Homeless Street Outreach: Spark for the Journey to a Dignified Life -- Youth Homelessness: A Global and National Analysis of Emerging Interventions for a Population at Risk -- Incorporating Youth Voice into Services for Young People Experiencing Homelessness -- "If I Don't Fight for It, I Have Nothing": Supporting Students Who Experience Homelessness While Enrolled in Higher Education -- Practice Dilemmas, Successes, and Challenges in the Delivery of Homeless Services: Voices from the Frontline.
Keywords: Social service; Public health; Social policy; Social Work; Public Health; Social Policy